ANALISA CELAH BUSI TERHADAP KONSUMSI BAHAN BAKAR BEIJING 100 CC - Suwandono .; Rusnoto .; Tofik Hidayatulloh (Engineering : Jurnal Bidang Teknik, 2011)
Spark plug  gap  effect  on  fuel  consumption of  100  cc  motorcycle  beijing  inMechanical  Engineering  Faculty of Engineering Laboratory,  University  ofPancasakti TegalThe objectives of this study to find out which plugs a gap in terms of gasoline andalcohol and it can make  the design of fuel consumption can be as desired to practice. The  data collection  used  by  doing  the practice,  books  and  journals which  relevantand direct measurement of multi-tester data needed in researchThis study  is  one of  effort  to help  Mechanical  Engineering  Faculty of Engineering Laboratory,  University of  Pancasakti  Tegal. It’s one of requirement for students to do practice.Data analysis methods used in the spark plug gap effect on fuel  consumption is a100cc  motorcycle Beijing  test  data  to  test  research  has been  desired  by  the user  ornot  in the  study,  adequacy of  test  data, this analysis is  to  examine  data that  has beenhomogenized  is  feasible  or  not  to  be  basis  in  the calculation  and  the third is thepercentile of test methods to determine the ideal size of the existing data.In this research needs calculation data including, such as electric current, voltage,  time and length of hose to determine fuel level, this data is taken to determine the fuel consumption is used to determine the distance.To  see  clearly  its use  in  the operation  and  make it simple, we can use an alternator  that is placed  under the  motorcycle  seat  and  is associated  with  iron  leverto  measure  the torque  is  automatically.  The result from altenator data which used digital multi tester calculation for the speed of 2000 rpm by measuring spark plug gap is appropriate with this studyKeywords :  plugs a gap and gasoline